FITOINDICATION OF EDAPHOTOPE ECOLOGICAL REGIMES FOR CREATION OF ENGLISH OAK (QUERCUS ROBUR L.) FOREST PLANTATIONS - Tarnopylska, O. M. (Forestry and Forest Melioration, 2018)
Introduction The environmental factors and their suitability for oak plantations establishment were assessed on model objects in order to test the practicability of using phytoindication during forest plantations creating, their further growing, revealing the relationships of vegetation with environmental (edaphic) factors, as well as monitoring condition. Materials and Methods The study was conducted in the Left-bank Forest-Steppe of Ukraine in fresh maple-linden oak site conditions (D2) in July. Objects of research were three model areas of forest plantations of English oak: 1 – 5-year old forest plantations created by 1-year old seedlings on a freshly felled area; 2 – 1-year old forest plantations created by planting the acorns into the holes in furrows on freshly felled area immediately after regeneration felling; 3 – 2-year old forest plantations created by 1-year old seedlings after converting felling. Scheme of planting beds is 3 ? 0.5–0.7 m. The conventional methods were used to study the site conditions type and forest type, forest growth and crop status and geobotanical description. Types of environmental regimes and satisfactoriness of environmental conditions of ecotypes were evaluated using phytoindication for 6 determining eco-factors (moisture, variability of moisture, acidity, salt regime of soils, level of nitrogen-containing and light-shading) by the average points method by Tsyganov on the base of average gradation indexes of all informative kinds taking into account the projective cover and superimposing of average values of environmental regimes of test sites on ecological amplitudes of English oak. Results The results of phytoindication analysis have shown that the intermediate regime between xerophytic forest-meadow and moist forest-meadow regimes (11.7–12.1 points) is inherent for all investigated soil humidification variants. In oak plantations created by 1-year seedlings, the degree of soil moisture variability is intermediate between stable and relatively stable moisture (2.4 and 3.6 points, relatively), while in plantations grown from acorns it is characterized by slightly varying moisture (4.7 points). In plantations created from seedlings, soils are sufficiently rich in salts.This is equivalent to 6.5–6.8 points (a semi-megatrophic type of salt regime, salts-rich: 160 mg/l of HCO3’ – 4–16 mg/100 g of soil). Indicators of soil fertility of the area where the plantations were created by sowing acorns are slightly higher than in the other two variants and correspond to 8.4 points, so the soils belong to the intermediate type between rather salts-rich and salts-rich (sub-megatrophic glycophile type of salt regime with high salts concentration: 200 mg/l of HCO3’ – 15–40 mg/100 g of soil). Acidity soil regimes are similar in plantations created by sowing acorns and by planting 1-year old seedlings (8.3–7.5 points, respectively) and are characterized by sub-acidophile level (pH = 6.7, that is intermediate between the slightly acidic and neutral). In terms of acidity, soils of 5-year plantations belong to subacid type– 7.1 points (pH 5.5–6.5). Nitrogen regime in plantations created by 5- and 2-year seedlings is characterized by 7.2 and 6.8 points, respectively, which refers to rather nitrogen-rich soils (0.3–0.4 %), while in the sowing acorns variant it amounts to 6.2 points; this is intermediate between nitrogen-poor and rather nitrogen-rich soils (0.25–0.35 %). Thus, all studied eco-factor regimes show that the soil regime at investigated areas corresponds to the optimum tolerance amplitude zone of oak which is favorable for growing plantations. The daily light-shading regime in 5- and 2-year plantations created by seedlings is 4.8 and 4.5 points, respectively, which is corresponded to light wood luminosity. The lighting regime of 1-year old plantations created by sowing acorns is 3.6. The resulting figures indicate the intense formation of forest environment with a lower insolation and higher soluble nitrogen accumulation in the areas of forest plantations created by seedlings, compared to the plantations created by planting acorns. Higher levels of illumination (insolation) facilitate “pulling” the salts to the upper layers of soil that increases their mineralization and slows down organic matter destruction and nitrogen accumulation. Conclusions We prove the suitability and feasibility of phytoindication to assess edaphotope of areas both projected for the creation of forest plantations and forested. It was revealed that, in the early stages of oak plantation growth, forest environment developing is more intense in the areas where forest plantations have been created by seedlings than in the areas where they are created by acorns planting. This experiment requires further comparative studies at different stages of English oak planting.